PENGUATAN KOMUNIKASI PENDIDIKAN (GURU-WALIMURID-SISWA) DI ERA DISRUPSI: (Strengthening Educational Communication “Teacher-Parents-Student” In The Era Of Disruption) - Lalu Muhammad Samiuddin (Raqib: Jurnal Studi Islam, 2024)
One of the important things that influences student learning success is the establishment of effective communication between teachers and parents, teachers and students and parents and students. The purpose of this research is to determine the important role of communication from these three elements. The results of this research show that communication between these three elements has a significant role in student learning success. Teachers are able to establish communication with students as evidenced by effective classroom management. Teachers provide appropriate and accurate information to parents regarding student information. This is because teachers and parents have the same desire, namely to realize student success. Apart from that, maintaining communication ethics is a guideline mentioned in the Al-Qur'an, the Al-Qur'an even states it clearly with the sentences Qoulan sadida, qoulan layyinan, Qaulan baliigha. The terms mentioned in the Qur'an are a signal and guidance for humans, especially believers, that paying attention to ethics when communicating is very important. Maintaining communication ethics motivates students to improve their achievements and learning outcomes. Students who receive attention from teachers in the form of good treatment make them learn well. Likewise, attention from their parents in the form of trust and provision of learning needs is a factor that strengthens their enthusiasm for learning.